FACTORS ASSOCIATED WITH THE PRESENCE OF AEDES AEGYPTI LARVAE - Apriyani, Apriyani; Rahmatullah, Ilham; Wulandari, Kartina; Kusumawati, Rindha Mareta; Effendi, Wahyuni (HEARTY, 2026)
Samarinda City ranked third in Indonesia for dengue cases in 2023 with 867 confirmed cases and 3 deaths. The first rank is Balikpapan City (1019 cases) and Kutai Kartanegara Regency (1555 cases and 4 deaths). Bengkuring Health Center is the health center that has the most DHF patients in Samarinda City. The main objective of this study was to identify the presence of Aedes aegypti mosquito larvae in Samarinda City, especially in Sempaja Utara Urban Village. This study was conducted using cross sectional technique. A total of 98 respondents from 43 RTs in Sempaja Utara Urban Village using stratified random sampling. The dependent variable of the study is the presence of Aedes aegypti larvae, and the independent variable is draining water reservoirs as well as the location of water reservoirs. Based on the results of the above research, it can be concluded that there is no relationship between draining water reservoirs and the presence of Aedes aegypti larvae in Sempaja Utara Village (p-value> 0.05). While the location of water reservoirs has a relationship with the presence of Aedes aegypti larvae in Sempaja Utara Village (p-value < 0.05).